BBMRI-ERIC's contributions to research and knowledge exchange on COVID-19 - Holub, Petr; Kozera, Lukasz; Florindi, Francesco; van Enckevort, Esther; Swertz, Morris; Reihs, Robert; Wutte, Andrea; Valík, Dalibor; Mayrhofer, Michaela Th; BBMRI-ERIC community (European journal of human genetics, 2020)
During the COVID-19 pandemic, the European biobanking infrastructure is in a unique position to preserve valuable biological material complemented with detailed data for future research purposes. Biobanks can be either integrated into healthcare, where preservation of the biological material is a fork in clinical routine diagnostics and medical treatment processes or they can also host prospective cohorts or material related to clinical trials. The paper discussed objectives of BBMRI-ERIC, the European research infrastructure established to facilitate access to quality-defined biological materials and data for research purposes, with respect to the COVID-19 crisis: (a) to collect information on available European as well as non-European COVID-19-relevant biobanking resources in BBMRI-ERIC Directory and to facilitate access to these via BBMRI-ERIC Negotiator platform; (b) to help harmonizing guidelines on how data and biological material is to be collected to maximize utility for future research, including large-scale data processing in artificial intelligence, by participating in activities such as COVID-19 Host Genetics Initiative; (c) to minimize risks for all involved parties dealing with (potentially) infectious material by developing recommendations and guidelines; (d) to provide a European-wide platform of exchange in relation to ethical, legal, and societal issues (ELSI) specific to the collection of biological material and data during the COVID-19 pandemic.
Keywords: Pneumonia, Viral; pandemie; Humans; koronavirové infekce; Evropa; umělá inteligence; Pandemics; Coronavirus Infections; Public Health; veřejné zdravotnictví; lidé; šíření informací; Europe; mezinárodní spolupráce; International Cooperation; Artificial Intelligence; COVID-19; banky biologického materiálu; Practice Guidelines as Topic; Betacoronavirus; antivirové látky; Biological Specimen Banks; biomedicínský výzkum; klinické zkoušky jako téma; směrnice pro lékařskou praxi jako téma; Antiviral Agents; Clinical Trials as Topic; Datasets as Topic; Biomedical Research; SARS-CoV-2; datové soubory jako téma; virová pneumonie; Information Dissemination